Path integral approach to particle production in a spatially-flat Robertson-Walker spacetime with cosmic scale factors a(t)=ao cosh (at) and a(t)= ao sin (at) - Guevarra, Jonathan S. (Animo Repository, 1994)
Pair production of free scalar particles in a spatially-flat Robertson-Walker spacetime with cosmic scale factors a(t)=ao cosh(at) and a(t)=ao sin(at), that represent an open and a closed universe, respectively, is investigated. The amplitude of pair production was determined by considering the propagator of a particle to evolve from the time when an antiparticle was detected to the time when its corresponding particle was observed. The propagator for each scale factor was evaluated exactly using the Feyman path integral method. From this propagator, the production amplitude and the particle number were determined. Results were found to be consistent with previous studies.